Analytical Design of the Number of Blade Propeller for Study of Aerodynamics Characteristics using Flow Simulation - Vresdian, Devan Junesco; Hapsari, Anindya Ananda; Wilyanti, Sinka; Dionova, Brainvendra Widi; Pratama, Legenda Prameswono; Saleh, Yasya Khalif Perdana (Politeknik Sukabumi, 2023)
The selection of an appropriate number of blades for a propeller is a critical factor in the design and performance of UAVs. This study aims to analyze aerodynamics. The analytical methodology employed in this research involves computational fluid dynamics (CFD) simulations using state-of-the-art software. A parametric study is conducted to evaluate the effect of different blade numbers on various aerodynamic performance metrics, such as dynamic pressure, static pressure, velocity, and force (Y). These simulations are carried out over a range of operating conditions, including varying airspeeds and altitudes. Our findings reveal that the number of blades significantly influences the aerodynamic characteristics of the propeller. Based on the CFD results, the type of propeller generates a different characteristic of aerodynamics. It will produce more static pressure, dynamic pressure, and velocity if we add the number of blades to it. But, with the CFD process we know that if we need to generate more force, especially in the (Y) axis as the representation of thrust on UAV, we need to consider using a propeller with a 2-blade or 4-blade that generates more thrust efficiently with 367.79 N and 450.59 N respectively rather than 3-blade or 5-blade. Because if the number of blades is added it will cost more pressure either on dynamic or static and velocity value but not following by force (Y) value. Using 200 the trajectories are enough to represent the aerodynamic characteristic produced by each type of propeller.